2017
DOI: 10.1097/md.0000000000007109
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of eyeball rupture in patients with or without orbital fracture

Abstract: To summarize the clinical features of eyeball rupture with or without orbital fracture and explore the differences between them.In all, 197 patients were observed, and the following data were recorded: sex, age, time of injury, place of injury, cause of trauma, zone of eye injury, intraocular content prolapse, surgical methods and the therapeutic process, visual acuity after injury, and the final best corrected visual acuity. The results were analyzed for statistically significant differences.There was no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…A correlation between ocular injuries and orbit fractures has been detected by several authors previously, especially in the case of posterior and/or lateral extension of the fracture [28,29]. Of note, final visual prognosis is reported to be worse in severe eye trauma with associated orbit fracture [30]. Moreover, frontal bone fractures are known to be closely related to posttraumatic pneumocephalus, which was also seen more commonly in VSI patients in our study [31].…”
Section: Discussionsupporting
confidence: 79%
“…A correlation between ocular injuries and orbit fractures has been detected by several authors previously, especially in the case of posterior and/or lateral extension of the fracture [28,29]. Of note, final visual prognosis is reported to be worse in severe eye trauma with associated orbit fracture [30]. Moreover, frontal bone fractures are known to be closely related to posttraumatic pneumocephalus, which was also seen more commonly in VSI patients in our study [31].…”
Section: Discussionsupporting
confidence: 79%
“…Previous research has found that trauma caused by a blunt force is a more common cause of orbital fracture than trauma caused by a sharp object. [46][47][48] Similarly, blunt trauma causes globe ruptures and is more likely to involve the posterior aspect of the globe, zones 2 and 3. 47,49 The posterior region of the globe is sequestered from the surrounding environment; for this reason, posterior ruptures may not have as high a risk of contamination as anterior scleral or corneal open wounds and thus may be at a reduced risk of developing endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, about 50% of patients having rupture globe had associated multiple orbital wall fractures. In the study done by Chen X et al, 36 out of 197 eyes of a rupture globe, 32 eyes got injured due to RTA. Among them 15 eyes had rupture globe with orbital fracture.…”
Section: Clinical Profilementioning
confidence: 99%